Bakery Product Enrichment with Phenolic Compounds as an Unexplored Strategy for the Control of the Maillard Reaction - Valentina Melini; Domizia Vescovo; Francesca Melini; Antonio Raffo (Applied Sciences, 2024)
The Maillard reaction (MR) is one of the main reactions that occurs during the thermal processing of food. It contributes positively to the flavor, aroma, and color of food but also produces harmful by-products, including acrylamide and advanced glycation end products (AGEs). Bakery products are major staples consumed daily by people from all walks of life and of all ages; the identification of strategies to hamper acrylamide formation in bread and bread-like products is thus crucial for public health. Several strategies have been proposed to inhibit the MR in food processing, including biochemical approaches such as the use of enzymes; innovative technologies such as ohmic heating, pulsed electric field, high pressure processing, or encapsulation of metal ions; and the chemical modification of reactants, intermediates, or products of MR. Recently, phenolic compounds have been reported to have an inhibitory effect on the formation of harmful by-products resulting from the MR. The aim of this paper is, therefore, to provide a state-of-the-art overview of the use of phenolic compounds in the formulation of bakery products to inhibit the MR. A systematic review of the most up-to-date scientific literature was thus performed. It emerged that the inhibitory action was mainly investigated in bread. Phenolic extracts and powders obtained from plant-based foods have been included in the formulation of bakery products. The effect of pure phenolic standards was also considered.